EFFECT OF PULSED GALVANIC ELECTRO STIMULATION AND ULTRASUONBD ON BURN HEALING. A RANDOMIZED CLINICAL TRIALS - Eddine, Hassane kheir; ktaiche, Jamal; Radwan, Ghada; Abbas, Rami; Hassan, Khodor Haidar (European Scientific Journal, ESJ, 2015)
The goal of this study is to evaluate the effect of pulsed galvanic electro stimulation of high voltage and ultrasound on the healing of induced burn applied on rats. 48 rats (Sprague Dawley), mass between 300g and 400g, age between 3 months and 4 months. These rats are putted and the same experimental conditions of alimentation and hygiene. Rats are divided into 3 groups of 16 rats each. Each rat was induced to a uniform burn of second degree by a specific device fabricated specially to this study. Group ES undergoes a treatment of electro stimulation by a pulsed galvanic current of high voltage for 10 min daily during 2 weeks. Group US undergoes a treatment of pulsed ultrasound of 1w/cmÂ² for 2 minutes daily during 2 weeks Group control GC undergoes placebo treatment. Measure are done by digital camera, results are analyzed by specific program (AutoCad) on computer. Wound healing between the three groups are different and statistical tests ( T-tests and ANOVA) done between the two groups US and GC show no significant difference in the reduction of the surface of healing between them (Î±Ëƒ0.05), whereas the comparison between ES group and the two others group was significant (Î±Ë‚0.05). At the end of the second week of treatment, the best healing was presented in ES group where the wound was healed by 61.4 % whereas the groups GC and US were 11.9 % and 14.9 % respectively. Therefore the ES group have the best results between than others groups (GC and US).